THE ATTITUDES OF MEDICAL STUDENTS TOWARDS CLINICAL RELEVANCE OF HISTOLOGY - Waseem, Naureen; Rasheed, Aaqiba; Gill, Maria; Asad, Ayesha; Shamim, Muhammad Omar; Waseem, Fatima (Pakistan Armed Forces Medical Journal, 2021)
Objective of Study:The objective of this study is to have an insight on student’s attitudes regarding histology’s clinical relevance in public and private sector medical college.Methodology: A cross sectional survey for attitude analysis towards histology’s clinical importance was carried out among 200 third year medical students from private and public sector medical college. Thurdstone and Chave attitude analysis questionnaire was employed to find the attitude score.Results: Students of both public and private sector medical college show scepticism towards the clinical importance of histology. There was no marked difference in the attitudes of students of public and private sector medical college. Most data remained on the borderline of the attitude scale employed.Conclusion: This study provided useful information for the teachers that students do not appreciate the clinical importance of histology much. Teachers need to devise strategies and to work on the students helping them comprehend the importance of histology.